Analisis Penerapan Kurikulum Merdeka Belajar Di MI NW Nurul Haramain Narmada - Husairi, Husairi; Alwan, Muhammad Alwan; Herawati, Herawati; Hudayati, Nurul (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine how the Merdeka Curriculum is implemented by teachers at MI NW Nurul Haramain Narmada and to identify the challenges encountered in its application. The research adopts a descriptive qualitative approach with a field research design, carried out through direct observation at the research site to obtain both primary and secondary data, with interviews serving as the main data collection technique. The findings indicate that implementing the Merdeka Curriculum requires teachers to have a deep understanding of its concepts and application, which is gained through various training activities. However, challenges remain, as some teachers still require further guidance due to an incomplete understanding of the curriculum’s principles. To address these issues, the school conducts regular training sessions to enhance teachers’ understanding and practical skills. The main difference between the Merdeka Curriculum and the previous curriculum lies in the inclusion of project-based learning, which fosters collaboration among students and hones critical thinking skills. This approach has been effectively integrated into learning activities, aligning with students’ needs and encouraging their active participation.